Organic geochemical controls on the dermal absorption of polycyclic aromatic hydrocarbons from manufactured gasworks soils - Williams-Clayson, Alison (2024)
Brownfield sites, such as former manufactured gas plants (MGPs), hold potential for urban redevelopment. However, the soils in these areas are often contaminated with a variety of organic pollutants. Among these, polycyclic aromatic hydrocarbons (PAHs) are persistently found as mixtures in soil, with several PAHs being recognized as potentially carcinogenic. Human health risk assessments (HHRAs) establish estimates on the risks posed from individual PAHs, including the potential dermal bioavailability. However, the dermal bioavailability values of PAHs currently applied in HHRAs are based on a single study that does not comprehensively represent the complexities of PAH-soil interactions. The study's singular PAH spiking approach within a single soil type failed to account for the heterogeneous interplay between diverse PAHs, soil properties and environmental factors. Consequently, this previous study potentially overestimated the PAH availability in soil and creates uncertainty in any calculated dermal bioavailability. There is a shortage of research investigating the dermal bioavailability of a large diversity of PAHs from different soil types in real-world contaminated soils (not spiked), including no knowledge of the dermal absorption behaviour of alkylated PAHs (alkyl-PAHs) and a lack of research into the organic matter (OM) fractions influencing PAH dermal bioavailability. To address these gaps this thesis focuses on assessing the relationships between both parent and alkylated PAHs and the characterised bulk OM of real-world contaminated MGP soils. The aim is to ascertain whether characterised bulk OM contribute to variations in PAH distributions across MGP sites and industrial processes, as well as to explore their influence on in vitro human dermal bioavailability. In this work, quantification of PAHs was achieved through gas chromatography tandem mass spectroscopy (GC-MS/MS), while bulk OM is characterised using Rock-Eval(6) Pyrolysis (RE). Chapter 5 describes the employment of principal component analysis (PCA) to differentiate MGP processes based on PAH distributions, with the assistance of the RE parameters. The findings reveal distinctive signatures for MGP processes with oil associations and lower temperatures, from petrogenic signatures and contributions of heavier weight PAHs, whereas other processes were found challenging to identify. Varied quantities of alkyl-PAHs in MGP soils were identified, emphasising the need to investigate the dermal bioavailability of these compounds. Chapter 6 reports the measured dermal absorption (quantified as dermal fluxes) of 27 parent and alkylated high molecular weight (HMW) PAHs from real-world soils. Fluxes of the receptor solution (RS) and synthetic membrane are quantified, revealing that real-world contaminated soils influenced by environmental factors, lead to lower dermal fluxes compared to previous investigations using spiked soils. The majority of available HMW PAHs were measured in the membrane, showing that the membrane acted as a sink for PAHs released from soils, resulting in delayed diffusion of HMW PAHs into the RS. Notably, fluxes decrease with increases in the PAH ring number, highlighting the potential risks associated with low ring number PAHs including one alkyl-PAH group at longer exposure timesteps, a factor currently overlooked in HHRAs. Chapter 7 reports linear regression analysis relationships between RE parameters and RS fluxes of five MGP samples which indicated strong associations between HMW PAHs exhibiting high fluxes and specific RE parameters. However, it is important to acknowledge that these relationships were primarily driven by one sample exhibiting exceptionally high PAH concentrations and RE values. Nonetheless, RE demonstrates promise as a screening tool for characterising contaminated soil, particularly for PAHs with higher fluxes and stronger correlations estimated for the membrane fluxes. However, further investigations exploring a larger dataset of soils is recommended to verify assumptions and produce models capable of predicting the dermal bioavailability of HMW PAHs from soils. In summary, this research advances the knowledge of dermal bioavailability by investigating the largest number of different PAHs, including previously unstudied alkyl-PAHs, and demonstrating their potential risk for dermal absorption. Additionally, certain RE parameters offer promise for estimating PAH bioavailability in soil. By elucidating the complexities of PAH-soil interactions and assessing their influence on dermal absorption, this study enriches our understanding of PAHs' dermal bioavailability from real-world contaminated soils. This knowledge can contribute to the refinement of accurate HHRAs, particularly regarding the potential risks posed by a diverse set of PAHs in varied contaminated soil contexts.